Gully Types and Posssibilities of their Investigation - Jakab, Gergely (JOURNAL OF LANDSCAPE ECOLOGY, 2006)
Soil erosion is one of the most important process in recent landscape evaluation, especially on agricultural field. In the first time mainly the process of sheet erosion was investigated because it was believed the most important cause of soil loss. From the early 1980s the attention was turned to linear erosion. It was proved that the role of gully erosion in mass movement could be much more effective than sheet erosion The role of sheet erosion was overestimated in Hungary as well up to now. This is the reason of less attention to detailed investigation of linear erosion processes. Considerable parts of Hungary are covered by sediments which are vulnerable to erosion. On most of these parts the climatic and topographic conditions are also favourable from the point of view of gully appearance and development. The appeared gullies hinder tillage and the field around them has to be given up. Since recultivation is very expensive, the practice is to open a new dirtroad next to the former one, decreasing the area of the arable field. The most important factor in gully formation is human activity. The best defence is to stop the causes, collect and carry away the surface runoff from the slope although the problem of the formed gully still exists. The daily practice in Hungary – to fill the gullies with waste – is the worst “solution”, because this means the direct contamination of surface water.
Keywords: linear erosion; gully; rill